Can we heal Chagas infection? - Vega Royero, Shirlene Patricia (2014)
We present a model for the parasite-antibody dynamical competition between Trypanosoma rangeli and its antibodies during the acute phase of an infection in a mammal host. The model reproduces experimental data from murine models found in the literature and allows us to demonstrate that a preinfection with T. rangeli induces a temporary protective effect against Chagas disease. As the mammal immune system is able to eliminate a single T. rangeli infection, the host high antibody levels, needed to resist the Chagas infection, are reduced with time, returning the system to the initial healthy state. Our results suggest that a preinfection with T. rangeli could be used to reduce the in-house vectorial parasitemia through repeated vaccination of domestic animals.